Stronger and prolonged negative effects of one specific commercial organic fertilizer on an agrobiont spider compared with tillage and chemical fertilizer - Na Yu; Tianhong Xu; Fumin Shi; Weitong Wang; Ming Chen; Zewen Liu (Agriculture, Ecosystems & Environment, 2026)

A field assessment of pheromone formulation, synergists, and trapping systems for Chilo suppressalis (Walker) (Lepidoptera: Crambidae) - Yu-Lei Wang; Xiao-Ling Niu; Meng-Bo Guo; Junyan Liu; Jian-Yu Deng; Fumin Wang (Crop Protection, 2026)

W1/O/W2 emulsion stabilized by β-lactoglobulin/exopolysaccharides/epigallocatechin gallate complex: Protective effects on Lactobacillus plantarum A81 during storage, pasteurization and gastrointestinal digestion - Cuicui Duan; Yi Zhang; Hongru Wang; Siyang Sui; Hui Liu; Cheng Wu; Lin Ma; Fumin Ma; Xiaolei Li; Dan Li (Food Chemistry, 2026)

Unraveling the structure-activity relationships of herbicide Metamifop polymorphs: Enhanced weed control efficacy - Minghui Zhao; Qi Zhao; Shichao Du; Zifan Gu; Sheng-Tao Yang; Zhenguo Gao; Fumin Xue; Weitang Liu; Qinmei Zhong (Journal of Hazardous Materials, 2026)

Exploration of the hypoglycemic effect and mechanism of Lactobacillus plantarum LH36 on type 2 diabetic mice through intestinal flora and non-targeted metabolomics - Cuicui Duan; Hui Liu; Siyang Sui; Hongru Wang; Yinfei Xing; Yixue Sun; Lifan Liu; Fumin Ma; Xiaolei Li; Dan Li (Food Bioscience, 2026)

Structural identification and antioxidant activity of soybean protein isolate-exopolysaccharides-chlorogenic acid ternary complex - Cuicui Duan; Siyang Sui; Hongru Wang; Hui Liu; Yiming Yang; Yixue Sun; Lifan Liu; Fumin Ma; Xiaolei Li; Dan Li (Food Bioscience, 2026)

Study on the characteristics of W1/O/W2 emulsion delivery system stabilized by soybean protein isolate/(−)-epigallocatechin gallate/exopolysaccharides complex - Cuicui Duan; Cheng Wu; Hui Liu; Siyang Sui; Hongru Wang; Lin Ma; Fumin Ma; Xiaolei Li; Dan Li (Food Research International, 2026)

Integration of real-time NH4+-N control and spatial microbial engineering achieves high removals of nitrogen and carbon in a sequence anoxic-oxic-anoxic (SAOA) system - Chaolong Gao; Qianwen Sui; Qihe Tang; Junya Zhang; Bing Yan; Dawei Yu; Fumin Zuo; Shuanglin Gui; Zhibo Liu; Xiaoshan Hu; Yuansong Wei (Bioresource Technology, 2026)

Enhanced suppression of retrogradation and digestibility in waxy rice starch by engineered mutants of GtfC type 4,6-α-glucanotransferase from Geobacillus sp. - Dan Li; Yuwei Liu; Cuicui Duan; Fumin Ma; Byung-Hoo Lee; Xiaolei Li (Food Bioscience, 2026)

Mechanism of colloidal gas aphrons for enhanced reagent spreading and improved hydrophobicity of the surface of coal gasification fine slag - Daochang Che; Shengyu Liu; Fumin Zhao; Jianying Guo; Qilin Zhang; Xiaoyang Liu (Chemical Engineering Journal, 2026)

Heterojunction engineering of Co3S4 to modulate NiO for efficient electrooxidation of 5-hydroxymethylfurfural - Wenting Cai; Shuai Liu; Tongxue Zhang; Ke Fan; Xubin Zhang; Fumin Wang; Jing-Jing Lv; Xijun Liu (Chemical Engineering Journal, 2026)

Isolation and characterization of a novel reassortant H3N8 avian influenza virus from chickens in Eastern China - Ping Wang; Jiamin Fu; Han Wu; Linwei Zhu; Taoming Tang; Zhigang Wu; Linfang Cheng; Fumin Liu; Hangping Yao; Nanping Wu; Haibo Wu (Virus Genes, 2026)

Magnetic Fe-Mn spinel particle electrodes from red mud-shield slag wastes for 3D electrocatalytic dye degradation - Xinxin Li; Fumin Ren; Junshi Liu; Sibo Jia; Xiaoyu Ge; Houliang Guo (Journal of Environmental Management, 2026)

Amino acid substitutions associated with adaptation of novel H10N3 and H10N5 avian influenza viruses to mice - Ping Wang; Jiamin Fu; Han Wu; Linwei Zhu; Linfang Cheng; Fumin Liu; Hangping Yao; Nanping Wu; Haibo Wu (Archives of Virology, 2025)

Functional properties and sensitization of β-lactoglobulin were improved by covalent binding with exopolysaccharides and (−)-epigallocatechin gallate - Cuicui Duan; Yi Zhang; Cheng Wu; Siyang Sui; Hui Liu; Hongru Wang; Lin Ma; Xiaolei Li; Fumin Ma; Dan Li (Food Research International, 2025)

The effect and mechanism of Fe-modified coffee grounds hydrothermal carbon on the mass transfer efficiency of PMS and H2O2 advanced oxidation - Dahua Yu; Qingdan Liao; Xitong Li; Fumin Liu; Jingxin Huang; Huilin Guan; Yizong Huang (Journal of Water Process Engineering, 2025)

Evolution of Uniaxial Compressive Properties of Weathered Granite with Varying Weathering and Mineral Content - Peng Lin; Fumin Liu; Ruiyang Ma; Zhaoyang Wang; Huihui Xie; Jintao Kang (Geotechnical and Geological Engineering, 2025)

Improved corn phenology monitoring using translation and weighting of characteristic points from time-series vegetation index - Qinyan Zhu; Fumin Wang; Siting Chen; Dailiang Peng; Qiuxiang Yi; Liming He; Zhanyu Liu (Computers and Electronics in Agriculture, 2025)

Enhancement effect and mechanism of extraction of carbon from coal gasification fine slag Combining colloidal gas aphrons with bubble - Daochang Che; Shengyu Liu; Fumin Zhao; Jianying Guo; Lei Zhang (Chemical Engineering Journal, 2025)

High-efficiency and stable perovskite solar cells via bidentate chelation for facet-engineered growth of FAPbI3 (111) crystals - Song Zhang; Yucong Zhou; Zhitao Shen; Yingying Li; Jian Song; Yicong Gao; Zezhi Wang; Bohao Zhang; Chong Chen; Rong Liu; Ying Liu; Ruirui Cao; et al. (Chemical Engineering Journal, 2025)

Machine Learning of Element Geochemical Anomalies for Adverse Geology Identification in Tunnels - Ruiqi Shao; Peng Lin; Zhenhao Xu; Fumin Liu; Yilong Liu (Journal of Earth Science, 2025)

Ce-doped TiO2 supported RuO2 as efficient catalysts for the oxidation of HCl to Cl2 - Jiahui Liu; Fangyuan Dong; Yaqi Huang; Yanghe Fu; Xinqing Lu; Rui Ma; Fumin Zhang; Shuhua Wang; Weidong Zhu (Journal of Environmental Sciences, 2025)

An exploration of the interaction, structural characterization and anti-oxidative properties of proanthocyanidin and beta-lactoglobulin complex - Cuicui Duan; Mengchun Qin; Lifan Liu; Yixue Sun; Lin Cai; Lin Ma; Xiaolei Li; Fumin Ma; Dan Li (Food Research International, 2025)

An Objective Synoptic Analysis Technique for the Identification of Tropical Cyclone Remote Precipitation in China and Its Application - Li Jia; Chenchen Ding; Chunhua Cong; Fumin Ren; Yanan Liu (Journal of Ocean University of China, 2025)

Dynamic study of water distillation detritiation process startup using rigorous and ANN models - Zhiwei Zhang; Fumin Wang; Xiaohong Xiong; Zhengyu Zou; Shisheng Li; Changda Li; Jinhua Shi; Bingxin Zhu; Zheng Wang; Yang Qin; Yongwang Li; Qingzhao Liu; et al. (Journal of Water Process Engineering, 2024)

Utilizing cationic vacancies to enhance nickel-cobalt layered double hydroxides for efficient electrocatalytic urea oxidation reaction - Tongxue Zhang; Shuai Liu; Wenting Cai; Xinyuan He; Hongyu Wang; Bingxin Zhu; Yang Qin; Junqi Zhang; Xijun Liu; Xubin Zhang; Fumin Wang (Chemical Engineering Journal, 2024)

Different effects of resins and asphaltenes concentration of crude oil on sandstone wettability - Yaohui Xu; Gang Yan; Baofeng Hou; Kaiming Su; Fumin Zhang; Baolei Liu; Shanshan Li; Shouyu Zhao; Yan Liu (Fuel, 2024)

Alternations of antibiotic resistance genes and microbial community dynamics on shared bicycles before and after pandemic lockdown - Leshan Xiu; Haodong Liu; Yi Xie; Qinqin Hu; Huimin Li; Fumin Chen; Chenxi Wang; Yuqian Zhang; Liyuan Hou; Kun Yin (Science of The Total Environment, 2024)

Combining shape and crop models to detect soybean growth stages - Zihang Lou; Fumin Wang; Dailiang Peng; Xiaoyang Zhang; Junfeng Xu; Xiaolin Zhu; Yan Wang; Zhou Shi; Le Yu; Guohua Liu; Qiaoyun Xie; Changyong Dou (Remote Sensing of Environment, 2023)

Visible-light-induced photocatalytic CO2 reduction over zirconium metal organic frameworks modified with different functional groups - Yuexian Du; Guang'an Jie; Huilin Jia; Jiahui Liu; Jieyu Wu; Yanghe Fu; Fumin Zhang; Weidong Zhu; Maohong Fan (Journal of Environmental Sciences, 2023)

The mechanism of H2O in the superheated steam affecting the quality of in-situ pyrolysates of oil shale kerogen: Part B-favorable conversion of residues - Fumin Zhao; Bao Li; Daochang Che; Shengyu Liu (Fuel, 2023)

Modeling collective motion for fish schooling via multi-agent reinforcement learning - Xin Wang; Shuo Liu; Yifan Yu; Shengzhi Yue; Ying Liu; Fumin Zhang; Yuanshan Lin (Ecological Modelling, 2023)

Simultaneous measurement of multiple labile heavy metals in soils by diffusive gradients in thin film technique - Rui Chen; Jiaxing Liu; Guoyu Ding; Fumin Ren; Rongguang Shi; Jungang Lv; Jing Cheng (Journal of Soils and Sediments, 2023)

High-value recycling of waste tire rubber powder by wet mixing method - Kuanfa Hao; Wenchao Wang; Xiurui Guo; Fumin Liu; Yuan Xu; Shouyun Guo; Lichen Bai; Gongxu Liu; Miaomiao Liu; Lei Guo; Haichao Liu (Journal of Cleaner Production, 2023)

Mechano-chemical rubber reclamation using aminolysis products of waste flexible polyurethane foams as the devulcanizing agent - Wenchao Wang; Kuanfa Hao; Xiurui Guo; Fumin Liu; Yuan Xu; Shouyun Guo; Lichen Bai; Gongxu Liu; Lianen Qu; Miaomiao Liu; Lei Guo; Haichao Liu (Journal of Cleaner Production, 2023)

pH-responsive in situ gelling properties of thiolated citrus high-methoxyl pectin and its potential gel mechanism - Jinfeng Chen; Yanli Cui; Fumin Yang; Shenggui Zhang; Yunxiang Ma; Jia Liu (Food Research International, 2023)

Rapid emergence of a PB2 D701N substitution during adaptation of an H9N2 avian influenza virus in mice - Fan Yang; Xiaodi Zhang; Fumin Liu; Hangping Yao; Nanping Wu; Haibo Wu (Archives of Virology, 2022)

Exploring the environmental properties and resource utilization of construction waste in Beijing-Tianjin-Hebei region - Shuxin Hu; Fumin Ren; Jinming Jia; Can Cui; Changhong Guo; Nana Cui; Li Ma; Han Si; Tong Lu; Guotao Liu; Boyu Zhang; Junshi Liu (Environmental Science and Pollution Research, 2022)

Increased virulence of a novel reassortant H1N3 avian influenza virus in mice as a result of adaptive amino acid substitutions - Fan Yang; Xiaodi Zhang; Fumin Liu; Hangping Yao; Nanping Wu; Haibo Wu (Virus Genes, 2022)

Streptomyces akebiae sp. nov., a novel actinomycete isolated from rhizosphere soil of Akebia trifoliate - Ping Mo; Kaiqin Li; Jinhua Zhou; Fumin Zhou; Yazhi Chen; Xiaojia Lin; Xiaoyu Liu; Kerui Huang; Wansheng Zou; Jian Gao (Antonie van Leeuwenhoek, 2022)

Ecological and health risk assessment of heavy metals in soil and Chinese herbal medicines - Chunyan Meng; Peng Wang; Zhuolu Hao; Zhenjie Gao; Qiang Li; Hongxia Gao; Yingli Liu; Qingzhao Li; Qian Wang; Fumin Feng (Environmental Geochemistry and Health, 2022)

Ecological risk assessment of heavy metals in farmland soils in Beijing by three improved risk assessment methods - Rui Chen; Xuying Cai; Guoyu Ding; Fumin Ren; Qi Wang; Nuo Cheng; Jiaxing Liu; Lanxin Li; Rongguang Shi (Environmental Science and Pollution Research, 2021)

Isolation and characterization of two novel reassortant H5N6 avian influenza viruses from waterfowl in eastern China - Fan Yang; Yixin Xiao; Fumin Liu; Hangping Yao; Nanping Wu; Haibo Wu (Archives of Virology, 2021)

Development of a colloidal gold-based immunochromatographic strip test using two monoclonal antibodies to detect H7N9 avian influenza virus - Fan Yang; Yixin Xiao; Bin Chen; Liyan Wang; Fumin Liu; Hangping Yao; Nanping Wu; Haibo Wu (Virus Genes, 2020)

Development of an antigen-capture enzyme-linked immunosorbent assay and immunochromatographic strip based on monoclonal antibodies for detection of H6 avian influenza viruses - Fan Yang; Yixin Xiao; Lihua Xu; Fumin Liu; Hangping Yao; Nanping Wu; Haibo Wu (Archives of Virology, 2020)

Molecular characterization of H10 subtype avian influenza viruses isolated from poultry in Eastern China - Haibo Wu; Fan Yang; Fumin Liu; Xiuming Peng; Bin Chen; Linfang Cheng; Xiangyun Lu; Hangping Yao; Nanping Wu (Archives of Virology, 2019)

Assessing spectral indices to estimate the fraction of photosynthetically active radiation absorbed by the vegetation canopy - Dailiang Peng; Helin Zhang; Le Yu; Mingquan Wu; Fumin Wang; Wenjiang Huang; Liangyun Liu; Rui Sun; Cunjun Li; Dacheng Wang; Fubao Xu (International Journal of Remote Sensing, 2018)

Development of a TaqMan MGB RT-PCR assay for the detection of type A and subtype H10 avian influenza viruses - Fan Yang; Bin Chen; Fumin Liu; Xiuming Peng; Tao Sun; Hangping Yao; Haibo Wu; Nanping Wu (Archives of Virology, 2018)

Establishment of a multiplex real-time RT-PCR assay for rapid identification of H6 subtype avian influenza viruses - Fan Yang; Haibo Wu; Fumin Liu; Xiangyun Lu; Xiuming Peng; Nanping Wu (Archives of Virology, 2018)

Isolation and molecular characterization of an H5N1 swine influenza virus in China in 2015 - Haibo Wu; Fan Yang; Rufeng Lu; Lihua Xu; Fumin Liu; Xiuming Peng; Nanping Wu (Archives of Virology, 2018)

CASCIRE surveillance network and work on avian influenza viruses - Yuhai Bi; Weifeng Shi; Jianjun Chen; Quanjiao Chen; Zhenghai Ma; Gary Wong; Wenxia Tian; Renfu Yin; Guanghua Fu; Yongchun Yang; William J. Liu; Chuansong Quan; et al. (Science China Life Sciences, 2017)

Characterization of reassortant H1-subtype avian influenza viruses isolated from poultry in Zhejiang Province in China from 2013 to 2015 - Haibo Wu; Rufeng Lu; Xiuming Peng; Fumin Liu; Linfang Cheng; Nanping Wu (Archives of Virology, 2017)

Complete genome sequence of a novel avastrovirus in goose - Yuxuan Zhang; Fumin Wang; Ning Liu; Lin Yang; Dabing Zhang (Archives of Virology, 2017)

High-throughput sequencing identifies HIV-1-replication- and latency-related miRNAs in CD4+ T cell lines - Xiangyun Lu; Jin Yang; Haibo Wu; Zongxing Yang; Changzhong Jin; Juan Wang; Linfang Cheng; Xiaorong Peng; Fumin Liu; Xiuming Peng; Sujing Ji; Huilin Ou; et al. (Archives of Virology, 2017)

Amino acid substitutions occurring during adaptation of an emergent H5N6 avian influenza virus to mammals - Xiuming Peng; Haibo Wu; Xiaorong Peng; Xiaoxin Wu; Linfang Cheng; Fumin Liu; Shujing Ji; Nanping Wu (Archives of Virology, 2016)

Evolutionary history of Apocheima cinerarius (Lepidoptera: Geometridae), a female flightless moth in northern China - Shuxian Liu; Nan Jiang; Dayong Xue; Rui Cheng; Yanhua Qu; Xinxin Li; Fumin Lei; Hongxiang Han (Zoologica Scripta, 2016)
The alterations in the phylogeographical structures of insects in response to the uplift of the Qinghai–Tibet Plateau and the Quaternary glaciations in eastern Asia, particularly in northern China, remain largely unknown. In this study, we selected Apocheima cinerarius , a moth with flightless females, using molecular data (complete mitochondrial genomes and nuclear data) and ecological niche modelling ( ENM ) to investigate the effects of paleoclimatic changes on the evolutionary history of insects in the area of northern China. The phylogenetic tree of complete mitochondrial genomes indicated that there were two lineages, the western and eastern lineages. The nuclear gene analyses also detected unique haplotypes in each lineage. Time of the most recent common ancestor ( TMRCA ) of the two lineages was approximately in Early–Middle Pleistocene. Bayesian skyline plots revealed that the western lineage underwent a population expansion event after the Last Glacial Maximum, whereas the eastern lineage underwent expansion between the Last Interglacial and the Last Glacial Maximum. Our results suggest that A. cinerarius expanded eastward from western sites until the moth was distributed across the entire region of northern China. Then, A . cinerarius underwent contraction into isolated glacial refugia followed by subsequent expansion driven by Pleistocene climate changes, which established a narrow sympatric area. Our results indicate that the Quaternary environmental fluctuations had profound influences on the diversification and demography of an insect in northern China, and the same species in north‐western China and north‐eastern China have different demographic histories.

Complete sequence of a novel duck astrovirus - Ning Liu; Fumin Wang; Dabing Zhang (Archives of Virology, 2014)

Estimating nitrogen concentration in rape from hyperspectral data at canopy level using support vector machines - Fumin Wang; Jingfeng Huang; Yuan Wang; Zhanyu Liu; Fayao Zhang (Precision Agriculture, 2013)

Anonymous single-copy nuclear DNA (scnDNA) markers for Grey-cheeked Fulvetta (Alcippe morrisonia) and Rufous-capped Babbler (Stachyridopsis ruficeps) - Bin Gao; Yanhua Qu; Gang Song; Huatao Liu; Fumin Lei (Conservation Genetics Resources, 2012)

Variation in baseline corticosterone levels of Tree Sparrow (Passer montanus) populations along an urban gradient in Beijing, China - Shuping Zhang; Fumin Lei; Shenglin Liu; Dongming Li; Cong Chen; Peizhe Wang (Journal of Ornithology, 2011)

Validation of artificial neural network techniques in the estimation of nitrogen concentration in rape using canopy hyperspectral reflectance data - Yuan Wang; Fumin Wang; Jingfeng Huang; Xiuzhen Wang; Zhanyu Liu (International Journal of Remote Sensing, 2009)

Changes of Climate Extremes in China - Panmao Zhai; Anjian Sun; Fumin Ren; Xiaonin Liu; Bo Gao; Qiang Zhang (Climatic Change, 1999)